Comparison of Direct Gram Stain directed Antibiotic Susceptibility testing with Standard Disk Diffusion Method in Urine - Niazi, Asima (International Journal of Pathology, 2023)
Background: Majority of Urinary tract infections are treated empirically. This not only results in antibiotic resistance in current patient but also there is spread of the resistance in community. Objective: To compare direct antibiotic susceptibility testing method in urine with standard disk diffusion method. Methods: The cross-sectional descriptive study was conducted at Armed Forces Institute of Rawalpindi Pakistan. Direct antimicrobial susceptibility was done after performing Gram stain on urine samples containing > 5 pus cells. The Gram stain of sample containing >2 Gram negative rods (GNR) was further processed. Results of Direct susceptibility were compared with Standard disk diffusion testing and minor, major and very major errors were calculated. Agreement between two methods was calculated by Pearson coefficient and significance was calculated by using T test. Result: Out of the 70 samples with Gram negative rods on Gram stain,54.2% were minor, 12.85% were major and 4.29% were vey major errors. The Pearson Coefficient was 0.866 which was high positive. The P value was (<0.01), it was statistically significant. Conclusion: Direct susceptibility of urine culture produced reliable results for majority of the antibiotics. Though not recommended, Direct Susceptibility Testing can be used in patients giving the clinician a preliminary report before the results of AST are available.